Using acoustic emissions to enhance fracture toughness calculations for CCNBD marble specimens - K. Kaklis; S. Mavrigiannakis; V. Saltas; F. Vallianatos; Z. Agioutantis (Fracture and Structural Integrity)
Rock fracture mechanics has been widely applied to blasting, hydraulic fracturing, mechanical fragmentation, rock slope analysis, geophysics, earthquake mechanics and many other science and technology fields. Development of failure in brittle materials is associated with microcracks, which release energy in the form of elastic waves called acoustic emissions. In the present study, acoustic emission (AE) measurements were carried out during cracked chevron notched Brazilian disc (CCNBD) tests on Nestos marble specimens. The fracture toughness of different modes of loading (mode-I and –II) is calculated and the results are discussed in conjunction with the AE parameters.